Safety and effectiveness of a novel neuroprotectant, KUS121, in patients with non-arteritic central retinal artery occlusion: An open-label, non-randomized, first-in-humans, phase 1/2 trial - Ikeda, Hanako Ohashi; Muraoka, Yuki; Hata, Masayuki; Sumi, Eriko; Ikeda, Takafumi; Nakagawa, Takayuki; Abe, Hiroyasu; Tada, Harue; Morita, Satoshi; Kakizuka, Akira; Yoshimura, Nagahisa; Tsujikawa, Akitaka (PLOS ONE, 2020)
Kyoto University Substance (KUS) 121, an ATPase inhibitor of valosin-containing protein, is a novel neuroprotectant. We tested the safety and effectiveness of KUS121 in patients with acute central retinal artery occlusion (CRAO). We conducted an investigator-initiated, first-in-humans, phase 1/2 clinical trial. Nine patients with non-arteritic CRAO symptoms lasting for 4–48 h were enrolled. These patients received daily intravitreal injections of KUS121 for 3 days: 25 μg (low-dose) in the first three patients and 50 μg (high-dose) in the next six patients. The primary endpoint was the safety of the drug. As a secondary endpoint, pharmacokinetics was evaluated. Other key secondary endpoints were changes in best-corrected visual acuity (BCVA), measured using the Early Treatment Diabetic Retinopathy Study chart, visual field scores, and retinal sensitivities between baseline and week 12; and decimal BCVA at week 12. Administration of KUS121 did not result in serious adverse events. All nine patients (100%) showed significant improvement of BCVA. Average readable letter counts, visual field scores, and retinal sensitivities also improved. Decimal BCVA at week 12 was better than 0.1 in four patients (44%) and equal to or better than 0.05 in seven patients (78%). This first-in-humans clinical trial provides support for the safety and efficacy of intravitreal KUS121 injection. To substantiate the safety and effectiveness for patients with acute CRAO, further larger scale clinical studies will be needed.